2010
DOI: 10.1007/s00198-010-1170-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical bone density with normal trabecular bone density in girls with Turner syndrome

Abstract: TS is associated with reduced BMAD at the femoral neck; pQCT data suggests that cortical density is reduced with sparing of trabecular bone. This differential of cortical and trabecular BMD may predispose to fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 25 publications
5
45
1
Order By: Relevance
“…This hypothesis owes to studies reporting lower aBMD of the one-third distal radius opposed to the ultradistal radius using DXA, (8,35) and lower cortical vBMD and/or cortical thickness in the proximal radius using pQCT. (18)(19)(20) Our results do not support the hypothesis of a selective cortical bone deficit in TS. On the contrary, TS patients in our study had compromised trabecular integrity in both radius and tibia, with significantly lower trabecular BV/TV and higher trabecular spacing.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This hypothesis owes to studies reporting lower aBMD of the one-third distal radius opposed to the ultradistal radius using DXA, (8,35) and lower cortical vBMD and/or cortical thickness in the proximal radius using pQCT. (18)(19)(20) Our results do not support the hypothesis of a selective cortical bone deficit in TS. On the contrary, TS patients in our study had compromised trabecular integrity in both radius and tibia, with significantly lower trabecular BV/TV and higher trabecular spacing.…”
Section: Discussioncontrasting
confidence: 99%
“…(38) Correspondingly, Soucek and colleagues (20) reported that when proximal radius cortical vBMD in TS patients was adjusted for partial volume artifacts, cortical vBMD rose from below normal to above normal reference values. Third, TS patients in our study were older (median age 35 years) compared to previous studies using pQCT (age range 6-25 years (18)(19)(20) ). Finally, participants in all studies had received varying amounts of GH and androgen therapy, which have both been shown to affect bone health.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Some authors observed reduced BMD at the femoral neck; QCT data suggests that cortical density is reduced with sparing of trabecular bone. This differential of cortical and trabecular BMD may predispose to fracture (56). There is an approximately 25% increase in fracture risk, most of which is related to medium or high-impact trauma.…”
Section: Bone Mass Gain and Prevention Of Fractures In Turner Syndromementioning
confidence: 99%